Political Action Day: A Student-Led Initiative to Increase Health Advocacy Training Among Medical Students - Gill, Harbir; Gill, Peter; Eardley, William; Marrie, Thomas (Canadian Medical Education Journal, 2010)
Background: Health advocacy is a critical aspect of the competent physician's role. It is identified as a core competency by several national physician regulatory organizations, yet few formal training programs exist. We developed an initiative to teach medical students health advocacy skills. Methods: At Political Action Day, students from Alberta medical schools lobbied the provincial government. A day of training seminars preceded Political Action Day that focused on teaching health advocacy and communication strategies. The following day, medical students met with elected representatives at the Legislative Assembly. An entry and exit survey was administered to students. Results: On October 26-27th, 2008, 40 students met with 38/83 (46%) elected representatives including the Minister of Health and Wellness. Feedback from students and politicians suggests the event was effective in teaching advocacy skills. This initiative inspired students to be politically active in the future. Conclusions: Political Action Day helps fulfill the health advocacy competency objectives, and requires minimal curriculum time and resources for integration. It is an effective tool to begin teaching advocacy, and should be further expanded and replicated at other Canadian medical schools.